2007
DOI: 10.1016/j.molcel.2007.06.031
|View full text |Cite
|
Sign up to set email alerts
|

mtRF1a Is a Human Mitochondrial Translation Release Factor Decoding the Major Termination Codons UAA and UAG

Abstract: SummaryHuman mitochondria contain their own genome, encoding 13 polypeptides that are synthesized within the organelle. The molecular processes that govern and facilitate this mitochondrial translation remain unclear. Many key factors have yet to be characterized—for example, those required for translation termination. All other systems have two classes of release factors that either promote codon-specific hydrolysis of peptidyl-tRNA (class I) or lack specificity but stimulate the dissociation of class I facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
170
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(182 citation statements)
references
References 40 publications
11
170
0
1
Order By: Relevance
“…Even though the bacterial and the mitochondrial ribosomes are bound to be rather different overall, the fact that the decoding region of the mitochondrial 9S and the bacterial 16S RNA are conserved in secondary structure 4,29 strongly suggests that this also pertains on the local three-dimensional structure. This is also supported by the strong sequence conservation between RF1 and mtRF1a in the decoding region, which, together with the fact that the experimentally observed specificity of mtRF1a on bacterial ribosomes 11,12 , is reproduced here, strengthens the reliability of our derived homology models.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Even though the bacterial and the mitochondrial ribosomes are bound to be rather different overall, the fact that the decoding region of the mitochondrial 9S and the bacterial 16S RNA are conserved in secondary structure 4,29 strongly suggests that this also pertains on the local three-dimensional structure. This is also supported by the strong sequence conservation between RF1 and mtRF1a in the decoding region, which, together with the fact that the experimentally observed specificity of mtRF1a on bacterial ribosomes 11,12 , is reproduced here, strengthens the reliability of our derived homology models.…”
Section: Discussionsupporting
confidence: 80%
“…This could be one reason for the limited effect on protein levels reported on mtRF1a depletion 12 . It is also a distinct possibility that mtRF1 is, in fact, the major release factor in vertebrate mitochondria, as mtRF1 has apparently not been tested in knockdown experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both of the domains involved in sequence recognition, however, are somewhat divergent in sequence and length but this was assumed to allow specificity for this expanded and unusual repertoire of four termination signals in human mitochondria. 10,11 Subsequent biochemical and in vivo analyses, however, failed to reveal any release activity associated with this protein. 12,13 After further bioinformatic mining, a second candidate emerged.…”
Section: Terminating Human Mitochondrial Protein Synthesismentioning
confidence: 99%
“…Both in vitro and in vivo analyses confirmed that mtRF1a was active on UAA and UAG triplets but no activity could be detected with AGA/ AGG codons positioned in the 70S E. coli ribosomal A-site. 11 This accounted for termination of eleven of the thirteen human mt-ORFs. It did not, however, resolve the question of which protein was responsible for release of polypeptides encoded by can recognise all three stop codons.…”
Section: Terminating Human Mitochondrial Protein Synthesismentioning
confidence: 99%